5.3.6 Problems 501 to 600

Table 5.295: Second order ode

#

ODE

Mathematica

Maple

1774

\[ {}x y^{\prime \prime }+\left (-2 x +2\right ) y^{\prime }+\left (x -2\right ) y = 0 \]

1775

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

1776

\[ {}x^{2} \ln \left (x \right )^{2} y^{\prime \prime }-2 x \ln \left (x \right ) y^{\prime }+\left (2+\ln \left (x \right )\right ) y = 0 \]

1777

\[ {}4 x y^{\prime \prime }+2 y^{\prime }+y = 0 \]

1778

\[ {}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

1779

\[ {}x^{2} y^{\prime \prime }-\left (2 a -1\right ) x y^{\prime }+a^{2} y = 0 \]

1780

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

1781

\[ {}x y^{\prime \prime }-\left (4 x +1\right ) y^{\prime }+\left (4 x +2\right ) y = 0 \]

1782

\[ {}4 x^{2} \sin \left (x \right ) y^{\prime \prime }-4 x \left (\sin \left (x \right )+x \cos \left (x \right )\right ) y^{\prime }+\left (2 x \cos \left (x \right )+3 \sin \left (x \right )\right ) y = 0 \]

1783

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-16 x^{2}+3\right ) y = 0 \]

1784

\[ {}\left (2 x +1\right ) x y^{\prime \prime }-2 \left (2 x^{2}-1\right ) y^{\prime }-4 \left (1+x \right ) y = 0 \]

1785

\[ {}\left (x^{2}-2 x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }+\left (2 x -2\right ) y = 0 \]

1786

\[ {}x y^{\prime \prime }-\left (4 x +1\right ) y^{\prime }+\left (4 x +2\right ) y = 0 \]

1787

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 4 x^{4} \]

1788

\[ {}\left (3 x -1\right ) y^{\prime \prime }-\left (3 x +2\right ) y^{\prime }-\left (6 x -8\right ) y = 0 \]

1789

\[ {}\left (1+x \right )^{2} y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }-\left (x^{2}+2 x -1\right ) y = \left (1+x \right )^{3} {\mathrm e}^{x} \]

1790

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = x^{2} \]

1791

\[ {}\left (x^{2}-4\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = x +2 \]

1805

\[ {}y^{\prime \prime }+9 y = \tan \left (3 x \right ) \]

1806

\[ {}y^{\prime \prime }+4 y = \sin \left (2 x \right ) \sec \left (2 x \right )^{2} \]

1807

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \frac {4}{1+{\mathrm e}^{-x}} \]

1808

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 3 \,{\mathrm e}^{x} \sec \left (x \right ) \]

1809

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 14 x^{{3}/{2}} {\mathrm e}^{x} \]

1810

\[ {}y^{\prime \prime }-y = \frac {4 \,{\mathrm e}^{-x}}{1-{\mathrm e}^{-2 x}} \]

1811

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 2 x^{2}+2 \]

1812

\[ {}x y^{\prime \prime }+\left (-2 x +2\right ) y^{\prime }+\left (x -2\right ) y = {\mathrm e}^{2 x} \]

1813

\[ {}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 4 \sqrt {x}\, {\mathrm e}^{x} \]

1814

\[ {}y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}+2\right ) y = 4 \,{\mathrm e}^{-x \left (x +2\right )} \]

1815

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = x^{{5}/{2}} \]

1816

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+3 y = 2 x^{4} \sin \left (x \right ) \]

1817

\[ {}\left (2 x +1\right ) y^{\prime \prime }-2 y^{\prime }-\left (2 x +3\right ) y = \left (2 x +1\right )^{2} {\mathrm e}^{-x} \]

1818

\[ {}2 x y^{\prime \prime }+2 y^{\prime }+2 y = \sin \left (\sqrt {x}\right ) \]

1819

\[ {}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 6 \,{\mathrm e}^{x} x^{3} \]

1820

\[ {}x^{2} y^{\prime \prime }-\left (2 a -1\right ) x y^{\prime }+a^{2} y = x^{a +1} \]

1821

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = x^{3} \cos \left (x \right ) \]

1822

\[ {}x y^{\prime \prime }-y^{\prime }-4 x^{3} y = 8 x^{5} \]

1823

\[ {}\sin \left (x \right ) y^{\prime \prime }+\left (2 \sin \left (x \right )-\cos \left (x \right )\right ) y^{\prime }+\left (\sin \left (x \right )-\cos \left (x \right )\right ) y = {\mathrm e}^{-x} \]

1824

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-16 x^{2}+3\right ) y = 8 x^{{5}/{2}} \]

1825

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}+3\right ) y = x^{{7}/{2}} \]

1826

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }-\left (x^{2}-2\right ) y = 3 x^{4} \]

1827

\[ {}x^{2} y^{\prime \prime }-2 x \left (1+x \right ) y^{\prime }+\left (x^{2}+2 x +2\right ) y = {\mathrm e}^{x} x^{3} \]

1828

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }-3 y = x^{{3}/{2}} \]

1829

\[ {}x^{2} y^{\prime \prime }-x \left (x +4\right ) y^{\prime }+2 \left (x +3\right ) y = {\mathrm e}^{x} x^{4} \]

1830

\[ {}x^{2} y^{\prime \prime }-2 x \left (x +2\right ) y^{\prime }+\left (x^{2}+4 x +6\right ) y = 2 x \,{\mathrm e}^{x} \]

1831

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (x^{2}+6\right ) y = x^{4} \]

1832

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 2 \left (x -1\right )^{2} {\mathrm e}^{x} \]

1833

\[ {}4 x^{2} y^{\prime \prime }-4 x \left (1+x \right ) y^{\prime }+\left (2 x +3\right ) y = x^{{5}/{2}} {\mathrm e}^{x} \]

1834

\[ {}\left (3 x -1\right ) y^{\prime \prime }-\left (3 x +2\right ) y^{\prime }-\left (6 x -8\right ) y = \left (3 x -1\right )^{2} {\mathrm e}^{2 x} \]

1835

\[ {}\left (x -1\right )^{2} y^{\prime \prime }-2 \left (x -1\right ) y^{\prime }+2 y = \left (x -1\right )^{2} \]

1836

\[ {}\left (x -1\right )^{2} y^{\prime \prime }-\left (x^{2}-1\right ) y^{\prime }+\left (1+x \right ) y = \left (x -1\right )^{3} {\mathrm e}^{x} \]

1837

\[ {}\left (x -1\right )^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = 2 x \]

1838

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = -2 x^{2} \]

1839

\[ {}\left (1+x \right ) \left (2 x +3\right ) y^{\prime \prime }+2 \left (x +2\right ) y^{\prime }-2 y = \left (2 x +3\right )^{2} \]

2362

\[ {}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0 \]

2363

\[ {}y^{\prime \prime }+t y^{\prime }+y = 0 \]

2364

\[ {}y^{\prime \prime }-y = 0 \]

2365

\[ {}6 y^{\prime \prime }-7 y^{\prime }+y = 0 \]

2366

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

2367

\[ {}3 y^{\prime \prime }+6 y^{\prime }+3 y = 0 \]

2368

\[ {}y^{\prime \prime }-3 y^{\prime }-4 y = 0 \]

2369

\[ {}2 y^{\prime \prime }+y^{\prime }-10 y = 0 \]

2370

\[ {}5 y^{\prime \prime }+5 y^{\prime }-y = 0 \]

2371

\[ {}y^{\prime \prime }-6 y^{\prime }+y = 0 \]

2372

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

2373

\[ {}t^{2} y^{\prime \prime }+\alpha t y^{\prime }+\beta y = 0 \]

2374

\[ {}t^{2} y^{\prime \prime }+5 t y^{\prime }-5 y = 0 \]

2375

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }-2 y = 0 \]

2376

\[ {}y^{\prime \prime }+2 y^{\prime }+4 y = 0 \]

2377

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

2378

\[ {}2 y^{\prime \prime }+3 y^{\prime }+4 y = 0 \]

2379

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

2380

\[ {}4 y^{\prime \prime }-y^{\prime }+y = 0 \]

2381

\[ {}y^{\prime \prime }+y^{\prime }+2 y = 0 \]

2382

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

2383

\[ {}2 y^{\prime \prime }-y^{\prime }+3 y = 0 \]

2384

\[ {}3 y^{\prime \prime }-2 y^{\prime }+4 y = 0 \]

2385

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

2386

\[ {}t^{2} y^{\prime \prime }+2 t y^{\prime }+2 y = 0 \]

2387

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

2388

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

2389

\[ {}9 y^{\prime \prime }+6 y^{\prime }+y = 0 \]

2390

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

2391

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

2392

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

2393

\[ {}y^{\prime \prime }-\frac {2 \left (t +1\right ) y^{\prime }}{t^{2}+2 t -1}+\frac {2 y}{t^{2}+2 t -1} = 0 \]

2394

\[ {}y^{\prime \prime }-4 t y^{\prime }+\left (4 t^{2}-2\right ) y = 0 \]

2395

\[ {}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+2 y = 0 \]

2396

\[ {}\left (t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+2 y = 0 \]

2397

\[ {}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+6 y = 0 \]

2398

\[ {}\left (2 t +1\right ) y^{\prime \prime }-4 \left (t +1\right ) y^{\prime }+4 y = 0 \]

2399

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-\frac {1}{4}\right ) y = 0 \]

2400

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0 \]

2401

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0 \]

2402

\[ {}y^{\prime \prime }+y = \sec \left (t \right ) \]

2403

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = t \,{\mathrm e}^{2 t} \]

2404

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = \left (t^{2}+1\right ) {\mathrm e}^{t} \]

2405

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = t \,{\mathrm e}^{3 t}+1 \]

2406

\[ {}3 y^{\prime \prime }+4 y^{\prime }+y = \sin \left (t \right ) {\mathrm e}^{-t} \]

2407

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = t^{{5}/{2}} {\mathrm e}^{-2 t} \]

2408

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sqrt {t +1} \]